R&D Investments under Endogenous Cluster Formation - Herbert Dawid; Tim Hellmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study investments in R&D and the formation of R&D clusters of firms which are competitors in the market. Firms first decide on long-term R&D investment, then form research clusters according to the unanimity game, and finally compete in quantities. Equilibria with no-investment might co-exist with equilibria where a large fraction of firms invest in R&D. Firms tend to over-invest compared to a scenario where research clusters are ex-ante fixed and also compared to the welfare optimum.
Keywords: C71; C72; L13; O30; 330